Correct answer to the quiz. Check your diagnosisMycosis fungoides – case report and short overview of the literature - Marszałek, Andrzej; Grzanka, Aleksandra; Grzanka, Dariusz; Placek, Waldemar (Polish Journal of Pathology, 2010)
Here we present a case report of a patient with mycosis fungoides (MF). A short overview of the currently used clinical algorithm and diagnostic methods is presented. The authors also provide a comparison of other T-cell skin lymphomas. The currently recommended disease staging is given.